Morphology of Placenta and its Relation with Small for Date Babies in 950 Live Births - Shirol1, Desai S. P1, V. B. Hukkeri3, R.D. Virupaxi1*, B. R. Potturi2 , V. S. (Recent Research in Science and Technology, 2011)
Incidence of low birth weight (LBW) and birth defects in the new born is a major health problem. This also may cause considerable financial stress to the parents and health facilities due to prolonged treatment in neonatal facility. This study was undertaken to assess morphology of placenta and its relation with LBW, babies in full term normal and small for gestational age group babies.Â This was a cross-sectional study of 950 placentae collected from Civil Hospital, Belgaum of which 636 were full term normal babies and 314 were of small for date babies. babies. Variables like placental weight and volume were studied. The results of the study indicated that both study variables mentioned above were significantly smaller in placenta of small for gestational age group infants. In full term control group, significant statistical correlation was found between birth weight to placental weight and placental volume. In small for gestational group babies also significant statistical correlation between birth weight to placental weight and placental volume was found but values were lower than control groups. Examination of placenta by obstetrician and pediatrician is important to throw light into prenatal life and provide information for the future care of mother and her offspring.